039 Positive findings in pre-participation examinations of middle-aged athletes, results of additional workup, and eventual disqualification rates. (3rd March 2020) - Dubnov-Raz, Gal; Neuman, Gil; Anat, Milman; Tomer, Ziv-Baran
Abstract : Background: Most studies on preparticipation examinations (PPE) and sudden cardiac death (SCD) in athletes focused on younger ages. The rate of sport-related SCD rises sharply above the age of 30, yet very few studies examined this population. Objective: To examine the rate of disqualification and its reasons after an initial PPE in competitive athletes older than 30 years, and the results of additional investigations. Design: Chart review of prospectively collected data. Setting: Sport medicine clinic of a large tertiary-care center. Participants: Competitive athletes older than 30 years who completed a PPE that included a stress test, from 2016 to 2019 (n=1, 312). Assessment of risk factors: Data collected were age, sex, sport type, cardiovascular risk factors, stress test results, reasons for disqualification and the recommended workup (when needed). Main outcome measurements: Primary outcomes: proportions of athletes disqualified following initial PPEs and ultimately after additional testing. Secondary outcomes: reasons for initial disqualification; recommended workup; predictors of positive PPEs using generalized estimated equations. Results: Eighty-five athletes (6.5%) were disqualified after initial PPE (age 51.2±8.5 years, 92% males, 72% with less than two cardiovascular risk factors). Reasons for disqualification were rhythm disturbances (49%), T-wave and ST-segment abnormalities on resting or stress electrocardiograms (46%), conduction abnormalities (7%) and others (3.5%)). A higher probability of initial disqualification was found in males (OR 3.12, CI 1.4–6.8) and with increasing age (OR per year 1.03, CI 1.01–1.05). Workup recommendations included mainly stress echocardiography (70%), 24-h Holter (34%) and resting echocardiography (25%). After workup, five athletes were ultimately disqualified (2 cardiomyopathy, 2 rhythm disturbances, 1 aortic dilatation). Thirteen athletes (15%) decided not to perform the recommended workup, as they had stopped competitive activity. Conclusions: The disqualification rate after an initial PPE in older competitive athletes was 6.5%, of which nearly all were men. After additional workup, 0.38% of PPEs resulted in complete disqualification. Various organizations can use these data to perform their individual assessments of cost/benefit.